Spices Mix Induces Biofilm Mode of Growth in Escherichia coli: Biofilm Producing Isolate of E. coli from Spices Mix - Mirani, Zulfiqar Ali; Khan, Muhammad Naseem; Aziz, Mubashir; Zehra, Lakht-E-; Sahir, Korish Hasnain; Khana, Seema Ismat (Biological Sciences - PJSIR, 2012)